Prática de higiene das mãos em uma clínica odontológica ensino - Carvalho, Nahida Ajala de (2016)
Adherence of healthcare workers to recommended hand-hygiene procedures is acknowledged as the most important practice in preventing healthcare-associated infections. However, adherence to hand hygiene remains unacceptably low, with rates usually below 50% in most hospitals. In fact, it stands as a challenge for infection control worldwide. In dental practice this issue, albeit important, has been little investigated. To evaluate hand hygiene practices in a school dental clinic before and after an educational campaign on hand hygiene. Current direct, prospective, observational study was undertaken between June and November 2015 in a university dental clinic to assess adherence in hand hygiene by 3rd, 4th and 5th year students, post-graduate students and professors (N=190) of the School of Dentistry, before and after an educational campaign on hand hygiene. The performance of the seven-step hand hygiene technique was also evaluated. Overall observation time reached 105 hours in one-and-a-half-hour sessions during the morning and afternoon shifts. Three covert observers registered 3152 opportunities for hands hygiene according to World Health Organization's Your 5 Moments for Hand Hygiene in dental settings. Overall adherence rate in hand hygiene reached 14%, or rather, 11% (175/1588) prior to the campaign and 17% (271/1564) after the campaign (P<0.001). The campaign increased adherence in hand hygiene at different moments for certain categories of participants. As a rule, adherence increased at moment 1 (before touching a patient) and moment 2 (before clean/aseptic procedure). Steps 2, 4, 5, 6 and 7 in the execution of hand hygiene technique were the most neglected prior to the campaign. Four of these steps revealed the most flaws in antisepsis training of hands with fluorescent alcohol gel during the campaign. There was a significant improvement in hand hygiene in 3rd year (steps 2, 4, 5, 6 and 7), 4th year (step 4) and post-graduate (steps 2 and 3) students. Further, 48% of responses on the importance of hand hygiene in dentistry were correct. Most undergraduate students (83%; 83 of 100) had never participated in a hand hygiene campaign or in an antisepsis training in hand hygiene with alcohol gel. Results revealed low adherence rate in hands hygiene and flaws in the execution of the technique. The hand hygiene campaign triggered a significant increase, albeit unacceptably low, in students´ and professors´ hand hygiene during patients´ dental care. Improvement in the hand hygiene technique for some categories of participants occurred after the campaign in spite of low adherence. Results also suggested the establishment of a continuous educational program on good practices in hand hygiene in a dental clinic to trigger adherence of hand hygiene and underscore its importance in dentistry care.